Soybean oversowing with Urochloa ruziziensis and corn as rotation crop - Correia, Nubia Maria (2015)
The objective of this work was to evaluate soybean oversowing with Urochloa ruziziensis, for the soybean capacity of dry mass production, for weed infestation, and corn crop development under no-tillage system. The experiment was carried out in a randomized complete block design, with four replicates, in a 2 x 5 + 1 factorial arrangement. Oversowing with U. ruziziensis was evaluated in two soybean growth stages (R-6 and R-8) and five seed quantities: 200, 400, 600, 800, and 1,000 points of cultural value (PCV). For control, a treatment without oversowing was kept. Oversowing of 200 PCV of U. ruziziensis, at the R-6 or R-8 soybean stages, results in a sufficient straw quantity for no-tillage system, and favors weed control in the rotation corn crop. However, in high amounts, U. ruziziensis straw over the soil affects corn plant height and grain production.